An interesting sexually dimorphic species, Neoribates isabelaensis sp. nov. (Acari, Oribatida, Parakalummidae) with remarks on sexual dimorphism in Oripodoidea - Bayartogtokh, Badamdorj; Ermilov, Sergey G.; Corpuz-Raros, Leonila (Zootaxa, 2017)
A new species Neoribates isabelaensis sp. nov. showing an interesting sexual dimorphism is described from bamboo litter on Luzon Island in the Philippines. This species is unique among other species of Neoribates in the structure of the posterior part of notogaster in males, which has a large round concavity bearing a pair of large sacculi S3. The specific function of this structure is not yet known, but the found sexual dimorphism is presumably involved in pheromonal communication allowing rapid sperm transfer. This is the fourth Neoribates species displaying sexually dimorphic characters. Additionally, Neoribates isabelaensis sp. nov. differs from the morphologically most similar species, Neoribates barbatus Hammer, 1968, by its smaller body size, pointed rostrum, long and setiform bothridial setae and the localization of notogastral setae h1 and h2, which insert close to each other. Further, we discussed all cases of sexual dimorphism in the family Parakalummidae as well as other related groups of Oripodoidea, and the possible function of these modifications.